2011
DOI: 10.1098/rsbl.2010.1094
|View full text |Cite
|
Sign up to set email alerts
|

An offspring signal of quality affects the timing of future parental reproduction

Abstract: Solicitation signals by offspring are well known to influence parental behaviour, and it is commonly assumed that this behavioural effect translates into an effect on residual reproduction of parents. However, this equivalence assumption concerning behavioural and reproductive effects caused by offspring signals remains largely untested. Here, we tested the effect of a chemical offspring signal of quality on the relative timing and amount of future reproduction in the European earwig (Forficula auricularia). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…2011), including the European earwig (Mas et al. 2009; Mas & Kölliker 2011). Although female condition is known to influence the period of maternal care (Laurien‐Kehnen & Trillmich 2004), current theoretical models do not incorporate female condition although female condition might be an important factor in shaping active choices by both sides (Bateson 1994).…”
Section: Discussionmentioning
confidence: 99%
“…2011), including the European earwig (Mas et al. 2009; Mas & Kölliker 2011). Although female condition is known to influence the period of maternal care (Laurien‐Kehnen & Trillmich 2004), current theoretical models do not incorporate female condition although female condition might be an important factor in shaping active choices by both sides (Bateson 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Upon the emergence of F1 adults, brothers and sisters from each first clutch were separated to prevent sibmating. After the 492 F0 mothers produced a second clutch or were characterized as single-clutch females (females are unlikely to produce additional clutches 60 days after the hatching of their first clutch [26]), F1 adults of the first-clutch families were assigned to two experimental groups, depending on their mother's relative investment in second clutches, as being in the bottom third (S-groups, including both singleand double-clutch producers) or in the top third (L-groups, including only double-clutch producers) of the distribution (each group includes 164 families, figure 1a). This relative investment, which is the number of eggs produced in second clutch divided by the total number of eggs produced, measures how mothers invested in second relative to first reproduction, while controlling for their overall capacity of egg production.…”
Section: Methodsmentioning
confidence: 99%
“…We selected 60 days as temporal delimiter for egg laying because previous work indicated that females were very unlikely to produce a second clutch more than 60 days after egg hatching (Mas and Kölliker 2011). Females laying a second clutch that did not hatch (N = 32) were discarded from the analyses as they could not be assigned unambiguously to the 1C or 2C tactic.…”
Section: Measures Of Maternal Carementioning
confidence: 99%